Akibat Hukum Perjanjian Perkawinan Yang Dibuat Dihadapan Notaris Terhadap Kreditur Sebagai Pihak Ketiga - Intan Pandini (Universitas Sriwijaya, 2018)
The marriage covenant is an agreement made by two people, a man and a woman, with the real purpose of forming a happy and eternal family based on belief in the one and only God as the first principle in Pancasila. A marriage will result in a marriage of wealth. The marriage agreement is an agreement between the prospective husband and the prospective wife to regulate the marital consequences of their property deviating from the union of wealth. In Article 147 of the Civil Code and Article 29 of Law Number 1 the Year 1974 concerning marriage, the legal act of making Marriage Agreements is made before or at the time of marriage takes place. However, with the issuance of Constitutional Court Decision No. 69 / PUU-XIII / 2015, there are some changes in the Marriage Agreement, which is still a pro and contra in society. The problems studied in this research is the effect of the Law of Marriage Agreement on the Creditor as a Third Party. The method used is normative legal research. The source of legal material used is primary and secondary sources in the form of books and legislation. The research shows that the legal consequences of the Marriage Agreement, made after the marriage by the Parties before the Notary, amends the legal mechanism for the making of the marriage agreement. It now can be made by a Notary without having to be preceded by requesting a judgment of the Court as long as the marriage bond takes place. Whereas the legal effect on the property that has been contracted to a third party, in this case, the creditor, is that the creditor can file the Lawsuit to the Court. If the Creditor can prove that the security of the debt or the agreement as collateral in any form acquired before the marriage agreement is made, then the Creditor may demand repayment of the joint property of the husband and wife.